2006
DOI: 10.1029/2006jd007392
|View full text |Cite
|
Sign up to set email alerts
|

Physical and optical properties of aerosols over an urban location in western India: Seasonal variabilities

Abstract: [1] We present results on various physical and optical properties of aerosols measured over Ahmedabad, an urban location in western India, from 2002 to 2005 and discuss their seasonal and interannual variabilities. Aerosol parameters which have been studied include AOD spectra, aerosol mass concentration, size distribution, BC concentration, wavelength dependency in absorption, scattering coefficient, single scattering albedo and their vertical distribution in the atmosphere. All data have been classified in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(110 citation statements)
references
References 69 publications
7
99
0
Order By: Relevance
“…However, our σ sp average value is relatively larger than the average values measured by Pereira et al (2008), at Evora, Portugal (46 Mm −1 ), and by Vrekoussis et al (2005), in remote areas of Greece and Turkey (50 and 45 Mm −1 ). Nevertheless, the measured σ sp values at Granada are lower than those obtained in highly polluted areas in US (Greenwald et al, 2007;Carrico et al, 2003) and are much smaller than those observed in large urban areas in Asia (Bergin et al, 2001;Andreae et al, 2008;Garland et al, 2008;Ganguly et al, 2006). These results indicate that Granada aerosol scattering coefficient values are typical of moderately polluted urban areas.…”
Section: Aerosol Scattering Absorption Coefficients and Aerosol Numbementioning
confidence: 53%
“…However, our σ sp average value is relatively larger than the average values measured by Pereira et al (2008), at Evora, Portugal (46 Mm −1 ), and by Vrekoussis et al (2005), in remote areas of Greece and Turkey (50 and 45 Mm −1 ). Nevertheless, the measured σ sp values at Granada are lower than those obtained in highly polluted areas in US (Greenwald et al, 2007;Carrico et al, 2003) and are much smaller than those observed in large urban areas in Asia (Bergin et al, 2001;Andreae et al, 2008;Garland et al, 2008;Ganguly et al, 2006). These results indicate that Granada aerosol scattering coefficient values are typical of moderately polluted urban areas.…”
Section: Aerosol Scattering Absorption Coefficients and Aerosol Numbementioning
confidence: 53%
“…For all ATR-42 flights performed during EUCAARI IOP, air mass back trajectories have been calculated from HYS-PLIT (Draxler et al, 2003) along the ATR flight path regardless of occurrence of the nucleation mode particles. For all ATR-42 flights, the prevailing atmospheric flows in the BL are given in Table 1.…”
Section: Air Mass Originsmentioning
confidence: 99%
“…Hence, the accuracy of MODIS-derived AOD is understood over several, though not all, locations of India. In addition, aerosol properties have been studied over India using a variety of in situ and remote-sensing measurements (Sagar et al, 2004;Dey et al, 2005;Devara et al, 2005;Ganguly et al, 2006;Krishna Moorthy et al, 2007;Srivastava et al, 2008;Kuniyal et al, 2009;Kaskaoutis et al, 2009;Vinoj et al, 2009;Pathak et al, 2010;Niranjan et al, 2011;Kumar et al, 2012;Lodhi et al, 2013;Verma et al, 2014). The aerosol scenario over India, study of anthropogenic and natural aerosols (Verma et al, 2011;Ramachandran et al, 2012), identification of pollution hot-spots (Di Girolamo et al, 2004), and the evolution and increase and/or decrease of pollution levels (Krishna over different timescales have also been studied.…”
Section: Introductionmentioning
confidence: 99%